2011
DOI: 10.1002/jssc.201100201
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ammonium in wastewaters by capillary electrophoresis on a column‐coupling chip with conductivity detection

Abstract: Analytical potentialities of a chip-based CE in determination of ammonium in wastewaters were investigated. CZE with the electric field and/or ITP sample stacking was performed on a column-coupling (CC) chip with integrated conductivity detectors. Acetate background electrolytes (pH ∼3) including 18-crown-6-ether (18-crown-6) and tartaric acid were developed to reach rapid (in 7-8 min) CZE and ITP-CZE resolutions of ammonium from other cations (sodium, potassium, calcium and magnesium) present in wastewater sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Ion chromatography [1,10,[23][24][25][26][27][28][29][30][31][32] has been also used for the determination of NH 4 + in waters in addition to spectrophotometry [33], CE [34], fluorimetry [14,35] and potentiometry [36,37]. Nevertheless, problems in the resolution of low molecular mass amine [1] and NH 4 + peaks as well as permanent damage of the column with consequent shortening of its life time can occur when high salinity water samples are directly analyzed [31].…”
Section: Liquid Chromatography 1455mentioning
confidence: 97%
“…Ion chromatography [1,10,[23][24][25][26][27][28][29][30][31][32] has been also used for the determination of NH 4 + in waters in addition to spectrophotometry [33], CE [34], fluorimetry [14,35] and potentiometry [36,37]. Nevertheless, problems in the resolution of low molecular mass amine [1] and NH 4 + peaks as well as permanent damage of the column with consequent shortening of its life time can occur when high salinity water samples are directly analyzed [31].…”
Section: Liquid Chromatography 1455mentioning
confidence: 97%
“…The enrichment factors were up to 780‐fold compared to a conventional CZE mode using UV detection and the LODs were in the 15–27 nM range. Luc et al described the determination of ammonium in wastewaters by CE on a column‐coupling chip with conductivity detection and with electric field and/or ITP sample stacking. Under preferred working conditions (suppressed hydrodynamic flow and EOF), the employed methods provided very good repeatabilities for both model and wastewater samples.…”
Section: Titpmentioning
confidence: 99%
“…For example, in the field of water analysis only a limited number of relevant papers can be found [7,16,[24][25][26][27]32]. Bodor et al [7] reported on isotachophoresis (ITP) determination of chloride, nitrate, sulfate, nitrite, fluoride and phosphate at pH 3.5 on a poly(methylmethacrylate) (PMMA) microchip using contact conductivity detection.…”
Section: Introductionmentioning
confidence: 98%
“…Although we can see significant efforts in developments of MCE [7,12,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], applications of this technology in analytical practice are still rather scarce. For example, in the field of water analysis only a limited number of relevant papers can be found [7,16,[24][25][26][27]32].…”
Section: Introductionmentioning
confidence: 99%